Molecular Evolution and Functional Divergence of the IgLON Family. (21st May 2018) - Kubick, Norwin; Brösamle, Desiree; Mickael, Michel-Edwar
IgLON family is a subgroup of cell adhesion molecules which is known to have diverse roles in neuronal development. IgLONs are characterized by possessing 3 Ig-like C2 domains, which play a part in mediating various cellular interactions. Recently, IgLONs have been shown to be expressed at the blood-brain barrier (BBB). However, our understanding of the genetic divergence patterns and evolutionary rates of these proteins in relation to their functions, in general, and at the BBB, in particular, remains inadequate. In this study, 12 species were explored to shed more light on the phylogenetic origins, structure, functional specificity, and divergence of this family. A total of 40 IgLON genes were identified from vertebrates and invertebrates. The absence of IgLON family genes in Hydra vulgaris and Nematostella vectensis but not in Drosophila melanogaster suggests that this family appeared during the time of divergence of Arthropoda 455 Mya. In general, IgLON genes have been subject to strong positive selection in vertebrates. Our study, based on IgLONs' structural similarity, suggests that they may play a role in the evolutionary changes in the brain anatomy towards complexity including regulating neural growth and BBB permeability. IgLONs' functions seem to be performed through complex interactions on the level of motifs as well as single residues. We identified several IgLON motifs that could be influencing cellular migration and proliferation as well as BBB integrity through interactions with SH3 or integrin. Our motif analysis also revealed that NEGR1 might be involved in MAPK pathway as a form of a signal transmitting receptor through its motif (KKVRVVVNF). We found several residues that were both positively selected and with highly functional specificity. We also located functional divergent residues that could act as drug targets to regulate BBB permeability. Furthermore, we identified several putative metalloproteinase cleavage sites that support the ectodomain shedding hypothesis of the IgLONs. In conclusion, our results present a bridge between IgLONs' molecular evolution and their functions.